ANALISA FAKTOR PSIKOSOSIAL IBU DENGAN KEJADIAN POST PARTUM BLUES - Siswi Wulandari; Bram Mustiko Utomo; Fauziah Laili; Kurnia Novita; Raras Sucma (Jurnal Ilmu Keperawatan dan Kebidanan, 2023)
The level of stress in postpartum mothers is influenced by several factors including psychosocial factors of the mother during pregnancy. The purpose of this study was to analyze the psychosocial factors of mothers during pregnancy with postpartum blues events. Correlational analytical design with a cross-sectional approach. The population in this study was all postpartum mothers at Arga Husada Hospital, Kediri Regency, which amounted to 19 respondents. Total sampling technique. Sample of all postpartum mothers at Arga Husada Hospital, Kediri Regency in 2022. The statistical test used is a proportion difference test using chi-square. Based on the table, the statistical value of chi-square is 2.809 with a significance of 0.245. Based on the table, the statistical value of chi-square was obtained at 0.386 with a significance of 0.824. Based on the table, the statistical value of chi-square was obtained at 0.686 with a significance of 0.407. Based on the table, the statistical value of chi-square was obtained at 0.853 with a significance of 0.356. Based on the table, the statistical value of chi-square was obtained at 0.672 with a significance of 0.412.  Based on the statistical test table, there is no significant relationship between the age of the number of pregnancies, occupations, and education with EPDS conditions